CONTRACTOR SAFETY MANAGEMENT SYSTEM (CSMS) - rusba, komeyni; Noeryanto, Noeryanto; Zulfikar, Iwan; Adolf Liku, James Evert; Pongky, Patunru; purwanti, Sri (Program Studi D4 K3 Universitas Balikpapan, 2022)
CSMS or Contractor Safety Management System is the documentation of a control mechanism in the form of a guide to ensure business standards in managing the performance of the Healthy Safety Environmental (HSE) of contractors. This system is used by the employer/owner in selecting contractors, supervising project implementation and evaluating the OHS system when the project has been completed. Therefore, it is necessary to introduce and create CSMS documents for contracting companies so that they can maintain work performance in the manufacturing industry, especially in oil and gas so as to increase business opportunities in the future. CSMS is a comprehensive system in the management of contractors from the planning stage to the execution of the work. The benefits of CSMS are CSMS Bridging the Company's OHSMS with the contractor's OHSMS, the Company provides requirements that must be met by OHSMS Contractor. For this reason, the company must have a good OHSMS, so that it can provide the basic framework for the development of the Contractor's OHSMS.